2015
DOI: 10.1039/c5cp00026b
|View full text |Cite
|
Sign up to set email alerts
|

Triply twisted Möbius annulene: a new class of two-photon active material – a computational study

Abstract: In the present work, we have studied the gas phase one- and two-photon absorption (OPA and TPA) properties of the first two excited states of the triply twisted Möbius annulene molecule (G. R. Schaller, et al., Nat. Chem. 2014, 6, 608) and five model systems substituted with different donor and acceptor groups. The main purpose of this study is to explore the OPA and TPA properties of this newly synthesized molecule and the unique π-conjugation provided by it. We have used the linear and quadratic response the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Theoretical calculations predict that upon irradiation with a strong laser pulse (even in the absence of a magnetic field), ring currents should be induced which are orders of magnitude larger than the currents induced in a superconducting NMR magnet 35,36. Moreover, peculiar nonlinear optical37 and two photon absorption properties38 have been predicted for Möbius annulenes.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical calculations predict that upon irradiation with a strong laser pulse (even in the absence of a magnetic field), ring currents should be induced which are orders of magnitude larger than the currents induced in a superconducting NMR magnet 35,36. Moreover, peculiar nonlinear optical37 and two photon absorption properties38 have been predicted for Möbius annulenes.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, it has been well-established in the literature that the computational theoryaided design can be a useful tool to optimize the molecular electro-optic performance. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Recently, several works [45][46][47][48][49][50][51][52][53][54][55] have evaluated the NLOP of Hückel and Möbius topologies. For instance, the present authors studied the electronic and vibrational contributions to static and dynamic NLOP of the Hückel-Möbius switch of the bianthraquinodimethane modified [16] annulene 56,57 and A,D-di-p-benzi [28]hexaphyrin(1.1.1.1.1.1).…”
Section: ) Introductionmentioning
confidence: 99%
“…16 Our previous results indicated that these systems present high NLOP values and large differences between the Hückel and Möbius structures, pointing out their potential use as optical switches. Kundi et al 53 analyzed the gas phase one-and two-photon absorption properties of the first two excited states of the triply twisted Möbius annulene molecule 58 and five model systems substituted with different donor and acceptor groups using the response theory and two-state model approaches. It was found that the unsubstituted molecule is completely two-photon inactive and it becomes active with the introduction of strong donor-acceptor groups.…”
Section: ) Introductionmentioning
confidence: 99%
“…DFT calculations on the triply twisted annulene 176 and related macrocycles were recently reported from other research groups. [287][288][289][290] Miki, Ohe, and co-workers recently reported the 2,2'-diethynyl-1,1'-binaphthyl-containing carbon double helices ( Figure 56). [291] The precursor (S,S)-177 wass ynthesized by using macrocyclization under Sonogashira-Hagihara coupling conditions.…”
Section: Thiophene Spacersmentioning
confidence: 98%
“…This molecule is the first example of a triply twisted Möbius annulene. DFT calculations on the triply twisted annulene 176 and related macrocycles were recently reported from other research groups …”
Section: Angle‐strained Alkyne‐containing π‐Conjugated Macrocyclesmentioning
confidence: 99%